A precision oncology approach to the pharmacological targeting of mechanistic dependencies in neuroendocrine tumors - Alvarez, Mariano J.; Jäger, Dirk (Nature genetics, 2018)
This study presents OncoTreat, a framework for the prioritization of compounds targeting mechanistic tumor dependencies in individual patients.